Nox enzymes in allergic airway inflammation - van der Vliet, Albert (Biochimica et biophysica acta, 2011)
Chronic airway diseases such as asthma are linked to oxidative environmental factors and are associated with increased production of reactive oxygen species (ROS). Therefore, it is commonly assumed that oxidative stress is an important contributing factor to asthma disease pathogenesis and that antioxidant strategies may be useful in the treatment of asthma. A primary source of ROS production in biological systems is NADPH oxidase (NOX), originally associated primarily with inflammatory cells but currently widely appreciated as an important enzyme system in many cell types, with a wide array of functional properties ranging from antimicrobial host defense to immune regulation and cell proliferation, differentiation and apoptosis. Given the complex nature of asthma disease pathology, involving many lung cell types that all express NOX homologs, it is not surprising that the contributions of NOX-derived ROS to various aspects of asthma development and progression are highly diverse and multifactorial. It is the purpose of the present review to summarize the current knowledge with respect to the functional aspects of NOX enzymes in various pulmonary cell types, and to discuss their potential importance in asthma pathogenesis. This article is part of a Special Issue entitled: Biochemistry of Asthma. ► NADPH oxidases (NOX) are a primary source of ROS production during chronic inflammation. ► NOX enzymes are critical in host defense, as well as tissue (re)generation and remodeling. ► The contributions of NOX enzymes to asthma pathology are multifactorial. ► Selective targeting of specific NOX enzymes may be useful in treatment of asthma.